Arbeitsmarktwirkungen der Mindestlohneinführung im Bauhauptgewerbe - Helmut Apel; Ronald Bachmann; Stefan Bender; Philipp vom Berge; Michael Fertig; Hanna Frings; Marion König; Joachim Möller; Alfredo Paloyo; Sandra Schaffner; Marcus Tamm; Matthias Umkehrer; et al. (Journal for Labour Market Research, 2012)
– On January 1st, 1997, minimum wages were introduced in the German main construction sector. We examine the effects of this wage regulation on various aspects of the labour market of this sector, particularly the effects on wages and employment. In East Germany, at the time of its introduction, the minimum wage was more strongly binding than in West Germany. Furthermore, the wages of a large fraction of the construction workforce in East Germany are close to the minimum wage, which is not the case in West Germany. Our results indicate that the wage floor significantly increased wage growth but had a negligible impact on employment of domestic workers. Because of data restrictions, a causal analysis of the effects on foreign establishments and their employees or on the self-employed is not possible. We caution against drawing conclusions from the results of our study for other industries given the specific characteristics of the main construction sector in Germany.
Keywords: J31; J38; 330; Mindestlohn - Erfolgskontrolle; Baugewerbe; Beschäftigungseffekte; Lohnhöhe; Mindestlohnrecht; Wettbewerbsfähigkeit; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland